2008
DOI: 10.1016/j.econedurev.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

College majors and the knowledge content of jobs

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Thus, non-cognitive skills provide an important explanation for the disparity in the fields that men and women study as well as in the occupations in which they are employed. This is consistent with previous research documenting the link between noncognitive skills and college enrollment (Jacob 2002), the effect of preferences on college major choices (Daymont and Andrisani 1984;Turner and Bowen 1999;Freeman and Hirsch 2008;Rosenbloom et al 2008), and the occupation-and gender-specific nature of the returns to noncognitive skills (Nyhus and Pons 2005;Mueller and Plug 2006;Cobb-Clark and Tan 2010). At the same time, there remains a large gap --despite our extensive controls --in the gender composition of the fields of study and occupations that men and women are entering.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, non-cognitive skills provide an important explanation for the disparity in the fields that men and women study as well as in the occupations in which they are employed. This is consistent with previous research documenting the link between noncognitive skills and college enrollment (Jacob 2002), the effect of preferences on college major choices (Daymont and Andrisani 1984;Turner and Bowen 1999;Freeman and Hirsch 2008;Rosenbloom et al 2008), and the occupation-and gender-specific nature of the returns to noncognitive skills (Nyhus and Pons 2005;Mueller and Plug 2006;Cobb-Clark and Tan 2010). At the same time, there remains a large gap --despite our extensive controls --in the gender composition of the fields of study and occupations that men and women are entering.…”
Section: Discussionsupporting
confidence: 80%
“…Second, although researchers have traditionally focused on the importance of gender differences in human capital and labor market discrimination, new estimates of the role of preferences in occupational choice are beginning to suggest that a substantial fraction of the gender gap in occupations may stem from men's and women's preferences over job attributes (Daymont and Andrisani 1984;Turner and Bowen 1999;Rosenbloom et al 2008;Zahfar 2009). Men are often shown to be more responsive than women to expected earnings when choosing their fields of study, for example (Freeman and Hirsch 2008;Montmarquette et al 2002;Boudarbat and Montmarquette 2007;Zafar 2009). This 3 disparity has profound implications for gender equity more generally.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, individual characteristics such as gender and parents education (Boudarbat and Montmarquette, 2009), tastes and motivations (Hilmer and Hilmer, 2012) or expected earnings (Arcidiacono et al, 2012;Beffy et al, 2012;Freeman and Hirsch, 2008) have been found to be important predictors for subject choice. Notably, differences in ability affect the subject choice of college majors (Turner and Bowen, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Berger (1988) stresses the importance of the streams of future earnings versus early income (at the time of the choice) as driving the students' choice of college majors. Freeman et al (2008) introduce the role of the knowledge content of a job. That is, the choice to undertake a specific major may be affected by the importance of the competencies provided by that major in the labor market, which may vary over years.…”
Section: Introductionmentioning
confidence: 99%